THE SYMBOLIC CONVERGENCE OF CROWDFUNDING IN POLITICAL CAMPAIGNS (CASE STUDY: NETIZEN DISCUSSIONS ON RIDWAN KAMIL`S FACEBOOK FANPAGE - Emeilia, Rindana Intan; Muksin, Nani Nurani (Jurnal Studi Pemerintahan, 2020)
Internet plays an important role as a medium of political communication, including its power for funding political campaigns known as crowdfunding. The success of crowdfunding in several countries, then adopted by Jabar Juara volunteers to raise funds political campaigns for Ridwan Kamil and Uu Ruzhanul Ulum in 2018 Governor Election. Socialization was carried out by uploading a video on title "Udunan Warga" (Funding from the Residents) which caused political conversation among virtual communities on Ridwan Kamil`s Facebook Fanpage. The existence of virtual communities in discussing political fundraising campaign ideas has an important role in supporting crowdfunding success. The reason is virtual communities have a potential to discuss shared interests and are very likely to have shared group consciousness to support crowdfunding movements.This article aims to explain the process of crowdfunding symbolic convergence on Ridwan Kamil's Facebook Fanpage. This study used a case study method and data collection techniques by online observation, in-depth interviews and documentation. The theory used was symbolic convergence which popularized by Ernest Bormann to see the construction of shared group consciousness among the Facebook user after seeing the video of Udunan Warga.The results showed that the crowdfunding mechanism carried out involved Jabar Juara volunteer as fundraisers, the site https://jabarjuara.id as a liaison platform and netizens/Facebook user as donors. The process of crowdfunding symbolic convergence in Ridwan Kamil's Faceboook Fanpage took place in stages ranging from basic structure, message structure, dynamic structure, communicator structure, medium structure and evaluative structure.